Managing age diversity in Singapore SMEs : exploring employees' perceptions towards younger and older workers. - Ng, Vivian Shi Ying. (2009)
Purpose – The purpose of this research is to examine the perceptions younger and older workers have of each other in Singapore Small and Medium-sized Enterprises (SMEs). Sufficiency of age diversity programs in these organizations was also examined.